Four New Cucurbitacins from the Fruit of Momordica charantia. Issue 11 (18th November 2014) - Chen, Jian‐Chao; Yuan, Xiao‐Xi; Zhou, Lin; Liu, Jie‐Qing; Nian, Yin; Li, Zhong‐Rong; Li, Yan; Xie, Ming‐Jin; Qiu, Ming‐Hua
Abstract Four new 5β, 19‐epoxycucurbitacins, kuguacins T–W (1–4, resp.), along with nine known cucurbitane derivatives, 5–13, were obtained from the fresh fruit of Momordica chrantia. Structures of the new metabolites were elucidated as 5β, 19‐epoxy‐25‐hydroxycucurbitane‐3, 7, 23‐trione (1), 5β, 19‐epoxy‐3, 7‐dioxo‐23, 24, 25, 26, 27‐pentanorcucurbitan‐22‐oic acid (2), 5β, 19‐epoxy‐3β‐hydroxycucurbit‐24‐ene‐7, 23‐dione (3), and 5β, 19‐epoxy‐25‐hydroxycucurbit‐23‐ene‐3, 7‐dione (4), by extensive spectroscopic investigations, which were confirmed by a single‐crystal X‐ray diffraction analyses in the case of compound 4.